Formation And Principles of Landscape Architecture of the Ancient City of Samarkand - Shakhlokhon Kosimova (Genius Journals, 2022)
This article discusses the landscape architecture of the ancient and Central Asian region of Samarkand and how it is formed. In particular, the landscape architecture, geographical structure and nature of the region were analysed.
Keywords: Arch-castle; urban plan; scenic trees; boulevard